Tata Kelola Dana BOS dan Transparansi Anggaran sebagai Determinan Kinerja Guru - Muhlasin Muhlasin; Muchtar Muchtar; Wijianto Wijianto (Journal of Public Power, 2024)
This study aims to analyze the effect of School Operational Assistance fund management and budget transparency on teacher performance at MTs Negeri 6 Madiun. The study employed a quantitative approach with descriptive and verification analysis. The population consisted of 38 teachers, and all members of the population were used as respondents through a saturated sampling technique. Data were collected through questionnaires, observation, and documentation, while the data were analyzed using multiple linear regression. The findings indicate that BOS fund management and budget transparency have positive and significant effects on teacher performance, both partially and simultaneously. The simultaneous contribution of the two independent variables reached 82.89 percent, indicating that school financial governance is a major determinant of teacher performance. Nevertheless, the implementation of BOS fund management and budget transparency has not fully reflected good governance principles because access to information, reporting discipline, and stakeholder participation remain limited. These conditions influence teacher performance in lesson planning, classroom implementation, learning evaluation, administrative completeness, and participation in additional school activities. The study emphasizes that effective, accountable, and transparent school financial governance can strengthen teacher motivation, improve the learning environment, and support sustainable educational quality.